2019
DOI: 10.3390/en12234540
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Influence of Multiple Factors on Transmission Efficiency of Loader Drive Axle

Abstract: In this study, a loader drive axle digital model was built using 3D commercial software. On the basis of this model, the transmission efficiency of the main reducing gear, the differential planetary mechanism, and the wheel planetary reducing gear of the loader drive axle were studied. The functional relationship of the transmission efficiency of the loader drive axle was obtained, including multiple factors: the mesh friction coefficient, the mesh power loss coefficient, the normal pressure angle, the helix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The drive axle assembly is the pivotal system within the automobile chassis and encompasses various components such as the drive axle housing, the main reducer, the differential, the drive shaft, and the wheel reducer. The transmission device mainly includes the main reducing driving gear, the main reducing driven gear, the differential planetary mechanism planet gear, the drive shaft gear, and the wheel planetary reducing planet gear [37]. Figure 1 illustrates the positioning of the drive shaft within the drive axle assembly.…”
Section: Drive Shaft and Failure Descriptionmentioning
confidence: 99%
“…The drive axle assembly is the pivotal system within the automobile chassis and encompasses various components such as the drive axle housing, the main reducer, the differential, the drive shaft, and the wheel reducer. The transmission device mainly includes the main reducing driving gear, the main reducing driven gear, the differential planetary mechanism planet gear, the drive shaft gear, and the wheel planetary reducing planet gear [37]. Figure 1 illustrates the positioning of the drive shaft within the drive axle assembly.…”
Section: Drive Shaft and Failure Descriptionmentioning
confidence: 99%
“…Li et al, reported "Integrated Analysis of Influence of Multiple Factors on Transmission Efficiency of Loader Drive Axle" [5]. In this study, a loader drive axle digital model was built using 3D commercial software.…”
Section: The Topic Of Energies and Its Applicationsmentioning
confidence: 99%
“…In an equally popular variant, angular velocities and torques are determined using the lever analogy method and nomograms [118][119][120][121][122][123][124][125][126][127][128][129][130]. Also very interesting is the combined method of determining the power flow and efficiency epicyclic transmission presented in references [131][132][133][134][135][136][137][138][139][140], where the Lagrange multipliers and kinematic constraints are used to determine the power flow and to verify the normal power flow balance. The accuracy is increased in this method by including virtual power in the analysis, where virtual power was determined in a non-inertial frame of epicyclic planetary gear.…”
Section: Introductionmentioning
confidence: 99%